2018
DOI: 10.7150/jca.24488
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Fenofibrate: A Repurposing Use

Abstract: Cancer is a leading cause of death throughout the world, and cancer therapy remains a big medical challenge in terms of both its therapeutic efficacy and safety. Therefore, to find out a safe anticancer drug has been long goal for oncologist and medical scientists. Among clinically used medicines with no or little toxicity, fenofibrate is a drug of the fibrate class that plays an important role in lowering the levels of serum cholesterol and triglycerides while elevating the levels of high-density lipoproteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 90 publications
4
69
0
Order By: Relevance
“…However, these studies were all conducted in rodents. Some investigators noted that rodent livers have a higher PPAR expression than do human livers . Our study is the first epidemiological study exploring the relationship between fibrate use and liver cancer.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…However, these studies were all conducted in rodents. Some investigators noted that rodent livers have a higher PPAR expression than do human livers . Our study is the first epidemiological study exploring the relationship between fibrate use and liver cancer.…”
Section: Discussionmentioning
confidence: 75%
“…In patients with hyperlipidemia, they selectively activate the peroxisome proliferator‐activated receptor‐α (PPAR‐α), reduce triglyceride levels, and increase high‐density lipoprotein concentrations . Recent accumulating biological evidence has suggested that PPAR‐α is vital in human cancer development and that fibrates are involved in cancer cell apoptosis, cell‐cycle arrest, and migration, making them prospective anticancer agents. Some experimental studies have further indicated that fibrates may reduce hepatocellular carcinoma cell proliferation via PPAR‐α–associated mechanisms .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other drugs such as L-NMMA (tilarginine acetate, a nitric oxide synthase inhibitor) [138], pro-viral integration moloney virus kinase (PIM)-1 inhibitors (olaparib) [139], L-asparginase [140], and fenofibrate [141] are being repurposed for breast cancer. These drugs were originally used in patients with cardiogenic shock, against viral infection, leukemia, helminthic infection, and in patients with high serum cholesterol and triglycerides, respectively.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%